2004
DOI: 10.3168/jds.s0022-0302(04)73466-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Estradiol Cypionate as a Substitute for GnRH in Protocols for Synchronizing Ovulation in Dairy Cattle

Abstract: Our purpose was to determine whether estradiol cypionate (ECP) could be substituted for the second GnRH injection of the standard Ovsynch protocol (injection of GnRH given 7 d before and 48 h after PGF(2alpha), with timed AI [TAI] 12 to 20 h after the second GnRH injection). Lactating dairy cows ranging from 61 to 82 d in milk at TAI were studied in 14 replicates. Main effects were hormone (ECP vs. GnRH) to induce ovulation and exposure to progesterone (P4) or not during the week preceding PGF(2alpha)-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 32 publications
2
30
0
4
Order By: Relevance
“…Cows treated with ECP had two surges of LH the first 25 h after treatment with ECP and the second after treatment with GnRH. This is a shorter interval than the 42 h interval from ECP treatment to the LH surge reported by Stevenson et al (2004); however, a greater dose of ECP was utilized in the present study. Cows in both the EB and CON treatments had a LH surge following treatment with GnRH.…”
Section: Discussionmentioning
confidence: 76%
“…Cows treated with ECP had two surges of LH the first 25 h after treatment with ECP and the second after treatment with GnRH. This is a shorter interval than the 42 h interval from ECP treatment to the LH surge reported by Stevenson et al (2004); however, a greater dose of ECP was utilized in the present study. Cows in both the EB and CON treatments had a LH surge following treatment with GnRH.…”
Section: Discussionmentioning
confidence: 76%
“…More recently, Presynch-Ovsynch protocol, which administers PGF 2α twice at a 14 d interval before Ovsynch/TAI, was developed [65]. Occurrence of estrus and ovulation before TAI during Ovsynch protocol can also be eliminated by using CIDR inserted from the day of Ovsynch to the PGF 2α administration (CIDR-Ovsynch) [66]. Heatsynch is basically similar to Ovsynch [67].…”
Section: Constraints Of Ovsynch/tai and Some Solutionmentioning
confidence: 99%
“…In terms of animal handling, the use of EC at device removal or GnRH at TAI as ovulatory stimuli requires is the same. However, several studies have reported on the use of GnRH 10-24 h before TAI (Pancarci et al 2002;Stevenson et al 2004;Sellars et al 2006;Souza et al 2008Souza et al , 2009Herlihy et al 2012;Ayres et al 2013). In these cases, the replacement of GnRH with EC at device removal can bring about the advantage of reducing animal handling by one time (Souza et al 2009).…”
Section: Discussionmentioning
confidence: 99%